Distinguishing features of Lycium L. species (family Solanaceae) distributed in Egypt based on their anatomical, metabolic, molecular, and ecological characteristics - Ragab, Osama G.; Mamdouh, Diaa; Bedair, Ramadan; Smetanska, Iryna; Gruda, Nazim S.; Yousif, Sawsan K. M.; Omer, Rihab M.; Althobaiti, Ashwaq T.; Abd El-Raouf, Hany S.; El-Taher, Ahmed M.; El-Sayed, Ashraf S.; Eldemerdash, Marwa M. (Frontiers in Plant Science, 2023)
Among the 70–80 species of the genus Lycium (family Solanaceae) disjunctly distributed around the world, only three are frequently distributed in different locations in Egypt. Due to the morphological similarities between these three species, there is a need for alternative tools to distinguish them. Thus, the objective of this study was to revise the taxonomic features of Lycium europaeum L., Lycium shawii Roem. & Schult., and Lycium schweinfurthii var. aschersonii (Dammer) Feinbrun in consideration of their anatomical, metabolic, molecular, and ecological characteristics. In addition to analysis of their anatomical and ecological features, DNA barcoding was performed for molecular characterization through internal transcribed spacer (ITS) sequencing and start codon targeted (SCoT) markers. Furthermore, metabolic profiling of the studied species was conducted based on gas chromatography–mass spectrometry (GC-MS). The observed anatomical features of the adaxial and abaxial epidermal layers, type of mesophyll, crystals, number of palisade and spongy layers, and the vascular system showed variations between the studied species. Beyond this, the anatomy of the leaves showed an isobilateral structure in the studied species, without distinct differences. Species were molecularly identified in terms of ITS sequences and SCoT markers. The ITS sequences were deposited in GenBank with accession numbers ON149839.1, OP597546.1, and ON521125.1 for L. europaeum L., L. shawii, and L. schweinfurthii var. aschersonii, respectively. The sequences showed variations in GC content between the studied species; this was 63.6% in L. europaeum, 61.53% in L. shawii, and 63.55% in L. schweinfurthii var. aschersonii. A total of 62 amplified fragments, including 44 polymorphic fragments with a ratio of 70.97%, were obtained in the SCoT analysis, as well as unique amplicons in L. europaeum L., shawii, and L. schweinfurthii var. aschersonii of 5, 11, and 4 fragments, respectively. Through GC-MS profiling, 38 compounds were identified with clear fluctuations in the extracts of each species. Of these, 23 were distinguishing chemicals that could help in chemical identification of the extracts of the studied species. The present study succeeds in identifying alternative clear and diverse characteristics that can be used to distinguish between L. europaeum, L. shawii, and L. schweinfurthii var. aschersonii.